Evolution of antibiotic consumption in pediatric outpatients of Asturias, Spain (2005-2018) - Laura Calle-Miguel; Ana Isabel Iglesias Carbajo; Gracia Modroño Riaño; Carlos Pérez Méndez; Elisa García García; Soledad Rodríguez Nebreda; Gonzalo Solís Sánchez (Elsevier, 2021)
Introduction: Data about consumption of antibiotics in Spain are worrisome. They are mainly prescribed in the community sector and there is a high exposure to antibiotics in the pediatric population. The aim of this study is to describe the evolution of antibiotic consumption in the pediatric population of Asturias during 2005-2018 period. Methods: Retrospective and descriptive study using data about consumption of antibacterial agents for systemic use (J01 group of the Anatomical Therapeutic Chemical Classification) in pediatric outpatients in Asturias between 2005 and 2018. Data, expressed as defined daily dose (DDD) per 1000 inhabitants per day (DID), in three periods were compared. Results: Mean antibiotic consumption in pediatric outpatients in Asturias (2005-2018) was 14 DID (CI95% 13.4-14.6). Consumption increased until 2009 (15.2 DID) and decreased from 2015 onwards (11.9 DID in 2018). Remarkable data along the study were: 1) increase in amoxicillin consumption (p = 0.027), that have exceeded that of amoxicillin-clavulanate since 2011; 2) steady consumption of macrolides, with an increase in azithromycin (p < 0.001) and a decrease in clarithromycin (p = 0.001); 3) reduction of cephalosporins consumption (p < 0.001); 4) increase in quinolones consumption (p = 0.002). Conclusions: Global antibiotic consumption in pediatric outpatients in Asturias between 2005 and 2018 has experienced a constant decrease lately and an improvement in patterns of antibacterial use. Resumen: Introducción: El consumo de antibióticos en España es elevado y más del 90% de las prescripciones se realizan en ámbito extrahospitalario. La exposición a antibióticos en la edad infantil es alta. El objetivo de este estudio es describir la evolución del consumo extrahospitalario de antibióticos en la población pediátrica del Principado de Asturias entre 2005 y 2018. Material y métodos: Estudio descriptivo y retrospectivo del consumo de antibacterianos de uso sistémico (grupo J01 de la clasificación ATC, Anatomical Therapeutic Chemical Classification) en ámbito extrahospitalario en la población pediátrica (0-13 años) del Principado de Asturias entre 2005 y 2018. Se compara el consumo, medido en número de dosis diarias definidas (DDD) por 1.000 habitantes y día (DHD), en 3 periodos de tiempo. Resultados: El consumo medio de antibacterianos en la población pediátrica asturiana (2005-2018) fue de 14 DHD (IC95% 13,4-14,6), con un aumento hasta 2009 (15,2 DHD) y descenso a partir de 2015 (11,9 DHD en 2018). A lo largo del estudio se detectó: 1) un aumento del consumo de amoxicilina (p = 0,027), que supera al de amoxicilina-clavulánico desde el año 2011; 2) un consumo estable de macrólidos, con un aumento de azitromicina (p < 0,001) y un descenso de claritromicina (p = 0,001); 3) un descenso del consumo de cefalosporinas (p < 0,001); 4) un aumento del consumo de quinolonas (p = 0,002). Conclusiones: El consumo de antibióticos a nivel extrahospitalario en la población pediátrica del Principado de Asturias entre los años 2005 y 2018 ha experimentado un descenso mantenido en los últimos años y una mejora evolutiva del patrón de uso.